Efektivitas Program Pendidikan Politik Badan Kesatuan Bangsa dan Politik Jawa Tengah dalam Menyambut Pemilu Serentak 2024 - Khasanah, Fela Uswatun; Saraswati, Annindya Putri (Jurnal Ilmiah Wahana Pendidikan, 2024)
In the 2019 General Election, Central Java Province was ranked second in Indonesia with the number of abstention voters (white group/not voting) of 5.52 million people or 19.79% of the total number of voters. This data shows the lack of awareness of the people of Central Java regarding democratic politics. In order to increase political awareness and the quality of democracy in the people of Central Java, the Central Java National and Political Unity Agency (Kesbangpol), as per its mission, has a political education program. This research focuses on the effectiveness of the political education public service program for the people of Central Java by the Central Java Kesbangpol in welcoming the 2024 simultaneous elections. The aim of this research is to analyze the effectiveness of the political education program that is already running. The method used in this research is a descriptive qualitative method with an inductive approach where researchers collect data through observation, interviews and documentation at the Central Java Kesbanpol Agency Office. The findings of this research show that the political education program organized by the Central Java Kesbangpol is quite effective in its implementation. Based on the results of this research, it can be concluded that the effectiveness of this program is supported by breakthroughs that minimize learning costs, compliance costs and psychological costs.